The impact of alcohol use on the outcomes of shoulder joint replacement in traumatic indications type of study: clinical study - comparison of functional outcomes of shoulder replacement in alcohol use disorder and control groups - Fulin Petr; Hert Jan; Walder Jiri; Kratochvil Adam; Kubasova Kristyna; Grzelecki Dariusz; Pokorny David (BMC Musculoskeletal Disorders)
Abstract Purpose Alcohol use disorder (AUD) is a medical condition characterized by an impaired ability to stop or control alcohol consumption despite adverse social, occupational, or health consequences. The aim of the study is to evaluate the outcomes of shoulder joint replacement in traumatic conditions in patients with AUD and compare them with the results of the control group. Methods We evaluated the outcomes of hemiarthroplasty and reverse shoulder arthroplasty divided into subgroups (AUD and control). The study includes a total of 238 patients with an average follow-up of 8 years. Clinical evaluation included the Constant Shoulder Score (CSS), abduction of the arm and pain. The results were statistically evaluated. Results We found no significant differences between the hemi-control and hemi-abusus groups in either measurement (CSS: p = 0.312, Cohen’s d = 0.262; abduction: p = 0.771, Cohen’s d = 0.073) or between the reverse-control and reverse-abusus groups in the abduction parameter (p = 0.394, Cohen’s d = 0.153). However, a significant difference was observed in the CSS parameter within the reverse group (p = 0.015, Cohen’s d = 0.447). Additionally, we identified a higher incidence of postoperative complications in patients with AUD for both implant types (hemi group: χ²(1) = 7.11, p = 0.0077; reverse group: χ²(1) = 11.25, p = 0.00080). Conclusions In this prospective study, we demonstrated the negative effect of alcohol use on the outcomes and function of shoulder joint replacements in cases of traumatic indications. The negative impact was observed following both hemiarthroplasty and reverse shoulder arthroplasty implantation. In both groups, a higher number of complications were recorded in patients with AUD.